Phenological stage of jaboticaba tree (Plinia cauliflora) in the chemical composition of the essential oil of the leaves and antioxidant activity: (Research, Society and Development, 2020)
Plants as Plinia cauliflora, a native Brazilian tree, could be a natural sources of safer antioxidants however there is no studies about the effects of the plant development stage on the essential oils (EO) or antioxidant activity. Objective: to evaluate the antioxidant activity, chemical composition and yield of essential oil from P. cauliflora leaves at phenological phases vegetative, flowering and fruiting. Methodology: the chemical composition was determined by gas chromatography coupled to mass spectrometry, and the antioxidant activity by three in vitro methods. Results: the leaf essential oil yield was the same for the vegetative, flowering and fruiting phases. The essential oil compounds have greater chemical diversity at flowering and fruiting phases. The higher antioxidant activity was obtained by β-carotene/ linoleic acid co-oxidation system. The oil from the vegetative phase protects 40.6% of β-carotene whereas the oils from the flowering and fruiting phases protect only 27.5% and 14.5% β-carotene, respectively. The analysis of the major compounds made evident that the predominant class were hydrocarbon sesquiterpenes with 67.0% (vegetative), 66.1% (flowering), and 59.4% (fruiting). The major compounds of EOs in the vegetative, flowering and fruiting phases were bicyclogermacrene (17.0, 14.5, and 11.0%), germacrene D (16.9, 15.9, and 12.4%) and trans-caryophyllene (9.2, 7.8, and 9.2%), respectively. In the vegetative phase, trans-2-hexenal (8.8%) and caryophyllene oxide (5.4%) stood out. Conclusion: P. cauliflora leaves are wasted after pruning and know about their essential oil could add value to jabuticaba production in Brazil.